The Ottoman Empire’s Struggle Against European Powers (Austria – Russia as a Case Study, 1740-1792) (The International Journal of Educational Sciences and Arts, 2025)
The Ottoman Empire directed its full weight toward military and combat development, equipping the army and building warships. It appears that the vast responsibilities and the expansion of their territories necessitated this effort, or that the very formation of their state was inherently military. However, by 1740, the Ottoman Empire experienced a significant decline in civilizational progress, enduring a prolonged period of stagnation and cultural inertia, while its rivals—chiefly Austria and Russia—began surpassing it in scientific and military advancements.Over time, European developments became more pronounced, while the Ottoman decline became increasingly evident, leading to psychological and intellectual defeatism. Meanwhile, a new power emerged to challenge the political balance in Europe, refusing to be part of any settlement between the Ottoman Empire and Europe—Russia. This new force, under the leadership of Tsar Peter the Great, aggressively sought to lift Russia out of backwardness. The Tsar worked to establish a powerful army and an even stronger navy capable of expanding Russia’s political and military influence. This ambition made conflict between Russia and the Ottomans inevitable, particularly in breaking the Ottoman dominance over the Black Sea, opening maritime routes for Russian ships, and securing the Bosporus and Dardanelles straits for Russian commercial vessels.Neither Peter the Great nor his successors acknowledged the Ottoman Empire’s political role in Europe. Consequently, various European states found it necessary to support the Ottoman Empire against Russia’s expansion, not out of affinity for the Ottomans, but to counterbalance Russian influence and preserve stability in Eastern Europe. Western European nations were unwilling to see Russian influence extend into Eastern Europe and the Balkans. Throughout the 18th century, the Ottomans managed to maintain their political presence in Europe, largely due to diplomatic support from European nations—except Russia—which ensured their continued existence.This study is significant as it highlights the conflict between the Ottoman Empire and the two major European powers, Austria and Russia, during the second half of the 18th century (1740-1792), a crucial historical period that shaped regional and international dynamics.
Keywords: Ottoman Empire; European Powers; Treaty; Austria; Russia; Moldavia; Wallachia; Bogdania